Broad-spectrum antimicrobial activity and in vivo efficacy of SK1260 against bacterial pathogens - Kavela, Sridhar; Kakkerla, Swetha; Thupurani, Murali Krishna (Frontiers in Microbiology, 2025)
IntroductionAntimicrobial resistance (AMR) is a growing global health concern, necessitating the development of novel therapeutic agents. Antimicrobial peptides (AMPs) have emerged as promising candidates due to their broad-spectrum activity and lower resistance potential. SK1260 is a newly developed AMP evaluated for its efficacy against Gram-positive and Gram-negative pathogens, including multidrug-resistant strains.MethodsThe antimicrobial activity of SK1260 was assessed through minimum inhibitory concentration (MIC) assays against clinical and reference strains of Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa. Time-kill kinetics were performed to evaluate bactericidal activity over time. In vivo efficacy was determined using murine infection models, where bacterial burden, tissue pathology, and survival rates were assessed following peptide administration.ResultsSK1260 exhibited potent antibacterial activity, with MIC values ranging from 3.13 to 12.5 µg/mL. Time-kill studies demonstrated dose- and time-dependent bactericidal effects, achieving complete bacterial clearance at concentrations ≥1× MIC, comparable to ciprofloxacin. In vivo studies revealed significant reductions in bacterial loads in vital organs, reduced histopathological damage, and improved survival in treated mice. Peptide treatment restored normal tissue architecture and showed efficacy equivalent to standard antibiotic therapy.DiscussionThe study establishes SK1260 as a promising broad-spectrum antimicrobial agent with efficacy against drug-resistant pathogens. Its ability to reduce bacterial burden and protect tissue integrity in vivo highlights its therapeutic potential. Further preclinical development and clinical trials are warranted to explore SK1260 as a viable alternative in the fight against AMR.